Problemas de la comercialización de banano (Musa paradisiaca), en el Ecuador.” - Mariscal Acosta, Arelis Sarai (2020)
Banana cultivation over time has experienced problems that affect the time of marketing the fruit both internally and externally. These problems correspond to factors such as crop diseases, transportation and banana quality. Due to the difficulties mentioned, this document will detail the problems that largely affect the commercialization of Ecuadorian bananas, knowing that the banana activity for more than half a century has been an important part in the development of Ecuador due to its economic participation (Gross Domestic Product) and social (sources of employment) generated during the banana production and marketing processes. The methodology will focus on gathering information through scientific articles, magazines, web pages, etc. It will also be based on the identification of problems that affect the quality of the banana when it is marketed. The information obtained was processed by means of the analysis, synthesis and summary technique, in order to make known about the problems of the commercialization of bananas in Ecuador. As previously detailed, it was determined that promoting the use of appropriate agricultural practices and correct post-harvest handling that allow maintaining the optimal quality of the fruit during the marketing process. Despite the humanitarian health problems that the different countries of the world are going through due to Covid - 19, Ecuador continues to export bananas, but there is no adequate marketing policy that guarantees fair price competition with informal producers.